THE NEXT DECADE IN ACCOUNTING. - Winter, S. G. (The Accounting Review, 1928)
Abstract The article presents views of the author about accounting in the next decade. Remarks made by me are classified under three major headings, the profession in general, the teaching of accounting and factors of major importance to accounting. The recognition of accounting as a profusion. Here it seems that the struggle for full and complete recognition must go on. If you tell me that accountants are recognized as members of a profession I shall ask, "by whom?" The expert accountant is desirous of full and complete recognition by the court; by all of the governmental divisions and subdivisions, by other professions and by the layman, not alone by one or two bureaus, a handful of clients and his fellow practitioners. He is to be confused with neither a bookkeeper nor an adding machine. To merit such recognition he must continue his efforts toward the attaining of those characteristics which are the hallmark of a professional man. The extension of accounting service and the broadening of the accountant's field of activity. We must admit from the outset that the accountant is in no immediate danger of reaching a saturation point in the demand for his services. There are still many managers and owners unconverted to the vital necessity of adequate accounting records.